Testing of transport system management strategy - Lupin, Sergey; Shein, Than; Kyaw Kyaw Lin; Davydova, Anastasia (Proceedings of IEEE East-West Design & Test Symposium (EWDTS 2014), 2014)
The paper discusses modelling of transport company management systems in a competitive environment. In order to analyse behaviour of the competing transport companies were modelled using an object-oriented structure. The criterion function applied for optimisation and implemented in the model was defined. The performance algorithm of a competitive environment was developed. To verify the proposed approach the model of transport company operating in a completive environment was simulated using AnyLogic software platform.